Analisis Rasio Keuangan Sebagai Tolok Ukur Kinerja Keuangan Badan Usaha Milik Desa (Bumdes) Arum Dalu Ngabar - Govindha Zahra Maharyani; Dwiati Marsiwi; Titin Eka Ardiana (ASSET: Jurnal Manajemen dan Bisnis, 2018)
BUMDes is a new line of business that is being promoted by the Government of the Republic of Indonesia. Establishment of BUMDes is intended to realize the Autonomous Village program. This study aims to determine the financial performance of BUMDes Arum Dalu Ngabar from 2015 to 2018. The assessment indicators are using Current Ratio, Debt to Equity Ratio, Return on Equity, Total Assets Turn Over, Net Profit Margin, and Return on Assets. The population in this study is all financial statements belonging to BUMDes Arum Dalu in 2015-2018. The sample used is the Arum Dalu BUMDes financial statements in 2015-2018. The data used are secondary data and data collection techniques by obtaining documents through other people. The data analysis technique in this study is the analysis of financial ratios. This study shows the results that the current ratio assessment is categorized Very Poor, with an average value of 2.492%. Debt to equity ratio is categorized Very Good, with an average value of 2.54%. Return on Equity is categorized as Fair, with an average value of 10.8%. Total assets turnover is categorized as Very Poor, with an average value of 0.19 times. Net profit margin in 2015-2018 is categorized Very Good with an average value of 51.5% and Return on assets is also categorized Very Good, with an average value of 10.5%. Based from the evaluation indicators of the Republic of Indonesia State Minister for Cooperatives, Small and Medium Enterprises Number. 06 / Per / M.KUKM / V / 2006 as a whole, the financial performance of BUMDes Arum Dalu is in the Fair category. Thus, the financial performance of BUMDes Arum Dalu really needs to be improved.